PENERAPAN QUALITY FUNCTION DEPLOYMENT (QFD) UNTUK MEMENUHI KEPUASAN PELANGGAN CV.TIRTA TAMANBALI – BANGLI - Ray Suwana, I Ketut; Tuningrat, Ida Ayu Mahatma; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
The aim of this study was to determine the customer satisfaction through Quality Function Deployment (QFD). This was a case study in CV. Tirta Tamanbali that producing drinking water located in Bangli regency. Design used in this research was Quality Function Deployment (QFD). QFD was used in order to gain voice customer and building house of quality to determine current product of CV. Tirta Tamanbali. Identification of attribute of customer interest, evaluation of customer satisfaction and customer interest are the purpose of this research. The result showed that attributes of customer interest are no moss, no taste, no smell, purity, hygienic manufacturing process, available in small and large shops, distribution channels reaching the whole Bali, resilience and strength of packaging, environmentally friendly, discounts for purchasing in large quantities, ergonomic packaging, available in various size, customer care, demineralization, oxygen, competitive price, and affordable to all segments of the market. Available in small and large stalls, distribution channels, resilience and strength of packaging did not meet the customer satisfaction.
Keywords: 36